METHODS OF RECOVERY OF CRT GLASS WASTE FROM WEEE - NICULA, Alin-Marius; POPIȚA, Gabriela-Emilia; ROȘU, Cristina (Studia Universitatis Babeș-Bolyai Ambientum, 2016)
This paper represents an ample study on hazardous waste came from WEEE, namely CRT glass. The aim of this study was to obtain a composite structural material which would integrate CRT (cone) glass. The hereby study is structured and presented into three main parts: literature data, the experimental part and results interpretation and general conclusions. Chemical analyzes were made with Atomic Absorption Spectrometry method and the lead (Pb) leachability of the new material made was monitored. Also mechanical strength test were made using a Tehnotest device. Mechanical tests were conducted for resistance to compression and flexure of the material. For the new material were obtained good results and it can be viable both from metal leachability and mechanical resistance point of view. The obtained data and results show the possibility to incorporate hazardous waste into new composite materials and represent a foundation for further research and new directions to follow are opened for profound investigation in this area.